Exploring the Interrelationship Between Economic Growth, Investment, and CO2 Emissions in Indonesia: A Time-Series Approach - Nano Prawoto (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the influence of economic growth, investment, industrial added value, trade value, and oil consumption on CO2 emissions in Indonesia in the period 1987-2019, before the COVID-19 pandemic. In addition, this study also considers the role of government policies in regulating carbon emissions and mitigating negative impacts on the environment. The method used in this study is the ECM (Error Correction Model) regression approach. The results show that in the long term, economic growth, industrial value-added, and oil consumption have a positive effect on increasing CO2 emissions in Indonesia, while investment (GFCF) and trade value have a negative effect on CO2 emissions. In the short term, industrial value added, and trade value have no significant effect on CO2 emissions, while economic growth and oil consumption encourage an increase in CO2 emissions. Investment (GFCF) contribute to the reduction of CO2 emissions. Indonesian government policies that focus on reducing carbon emissions through regulations that support renewable energy and energy efficiency, as well as controlling oil consumption, are expected to accelerate the transition to a low-carbon economy. The implication of these findings is that more assertive and integrated policies between the economic and environmental sectors are needed to effectively reduce CO2 emissions, while supporting economic growth and industrialization.